Green Synthesis of New Pyrrolo [1, 2-a] quinoxalines as Antiproliferative Agents in GPER-expressing Breast Cancer Cells. (31st October 2021) - Carullo, Gabriele; Mazzotta, Sarah; Giordano, Francesca; Aiello, Francesca
Abstract : 4, 5-Dihydropyrrolo [1, 2- a ]quinoxalines are interesting druggable scaffolds, with multifaceted biological properties, including anticancer properties targeting the G protein-coupled estrogen receptor 1 (GPER). In this work, the synthesis and preliminary antiproliferative activity of a small set of new 4, 5-dihydropyrrolo[1, 2- a ]quinoxalines (18-20) and pyrrolo[1, 2-a]quinoxalines (21, 22) has been reported, inspired by known antiproliferative agents (G-1, G-15, and G-36). The synthesis of the pyrroloquinoxalinic core was employed following the Pictet–Spengler reaction, using the surfactant p -dodecylbenzene sulphonic acid ( p -DBSA), as catalyst. It demonstrated efficiency in the catalysis of the 4-phenylpyrrole [1, 2- a ] quinoxaline type compound formation in mild solvents such as water, ethanol, and hydroalcoholic solutions. In addition, the reactions proceeded in a short time (between 15 and 120 minutes) at room temperature and with high yields. The in vitro MTT assays showed that the presence of isopropyl groups furnished promising antiproliferative compounds. Although, the acetyl group provided also antiproliferative effects, breaking down its responsibility in the GPER transactivation. Nevertheless, it is possible to conclude that the 4, 5-dihydropyrrolo[1, 2- a ]quinoxalines remain a feasible scaffold to develop anticancer agents against GPER-expressing cells.